Corrosion Mapping Solution Using dB-UT and Phased Array Transducers (Borneo Engineering & Advanced Multidisciplinary International Journal, 2025)
To improve the accuracy and efficiency of corrosion detection, decibel ultrasonic testing (dB-UT) and phased array techniques provide a significant solution for corrosion mapping. These techniques take advantage of dB-UT’s transducer capacity to evaluate corrosion severity using decibel drop measurements, whereas phased array transducers provide detailed imaging of the internal structure, allowing for the exact localisation of corrosion flaws. This study demonstrated the corrosion mapping on a steel pipe through a series of controlled experiments where corrosion patterns were accurately mapped across various scan plans. The results significantly improve detection limits, outperforming existing approaches and offering a high resolution of corroded images via a phased array transducer.